Performance evaluation of a steam-assisted incinerator using used oil fuels for diaper waste treatment under natural convection - Irawan, Ibnu; Budiarto, Hairil; Mubarok, Khamdi; Amandha, Yaumil Nurchoir (Jurnal Polimesin, 2025)
Incinerators offer an effective solution for waste processing by maintaining high combustion temperatures in a well-insulated and enclosed chamber. The combustion process using an incinerator has the ability to convert waste into steam gas and ash that can be utilized. The advantage of the incineration process is its ability to reduce the volume of waste significantly, with a reduction rate of more than 65%.  In this research, a water steam stove was fuelled by liquid waste namely used motor oil and used cooking oil. It was tested for its performance in burning diaper waste under natural convection. The stove used has a height of 370 cm, a nozzle diameter of 2 cm, and a water vapor flow rate of 0.75 kg/hour. This study aimed to evaluate the thermal efficiency of the incinerator and analyze the influence of natural convection, fuel type, and the number of air holes on combustion performance. Experimental results showed that using eight air holes produced optimal results. Combustion with used motor oil reached the highest temperature of 397°C, burned for 65 minutes, and left 0.68 kg of ash residue. In comparison, used cooking oil reached 381°C, burned for 89 minutes, and left 0.95 kg of ash. The difference in fuel boiling points and viscosity significantly affected combustion efficiency. The highest thermal efficiency was 87% when using used motor oil, compared to 35% for used cooking oil. These findings suggest that used motor oil is a more effective and efficient fuel for diaper waste incineration in naturally ventilated systems.